DEPARTURE OF IVAN STAMBOLIC IN KOSOVO POLJE ON APRIL 6, 1987 (Heritage, 2020)
The Serbian resistance movement, centered in Kosovo Polje, was a new factor in the complicated political relations of communist Yugoslavia. In the spring of 1986, this grassroots movement was becoming a formidable political force and a possible source of wider social unrest. The most influential politician in the Serbian leadership, Ivan Stamoblić, came to Kosovo Polje on April 6, 1986. During a short visit, he missed an opportunity to gain the movement's support and showed a lack of understanding of the deep changes in Yugoslav society.
Keywords: SAP Kosovo, Kosovo issue, Ivan Stambolić, Kosta Bulatović, Dobrica Cosić, Serbian Resistance Movement, Kosovo Polje